Utilization of Sleeping Peatlands Areas as Forage Feed Provider in The Intensive Beef Cattle Farming at Pelalawan District, Indonesia - Nawari Nawari; Rasoel Hamidy; Yusni Ikhwan Siregar; Sukendi Sukendi; Efriyeldi Efriyeldi (ECOTONE, 2021)
Pelalawan District has several sleep peatland areas, which overgrown with grass weeds. This area has the potential to become a sources of beef cattle farming feed in the intensive livestock system. The potential of the beef cattle market is still prospective as a source of protein demanded by the majority peoples. This study aims to valuate and evaluate the potential carrying capacity and economic value of sleep peatlands area as forage provider. This research method was descriptive approach. The data used in this study is secondary data collected from various reliable sources and previous related research. Carrying capacity was expressed by estimate the land's ability to provide cattle feed. Economic analysis is carried out by estimate profit which obtained from the intensive beef cattle farming system. The analysis results shows that sleep peatland areas that potential to supports intensive beef cattle farming around 3,210 ha with carrying capacity = 9,078 cows/year. This carrying capacity was higher than the current beef cattle population around 1,992 cows. The potential economic value reaches IDR 45.56 B/year, which is higher than the current actual economic around IDR 9.99 B. It’s necessary to improve management aspects by integrating the development of intensive cattle farming systems with community-based peatland restoration programs, corporate social responsibility, and SDGs achievement commitments. This requires a solid partnership among stakeholders that will increase the management dimension towards a more sustainable way.